2018
DOI: 10.1007/s13770-018-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Stem Cell Treatment for Type I Diabetes Mellitus

Abstract: BACKGROUND: Diabetes mellitus is a major health concern in current scenario which has been found to affect people of almost all ages. The disease has huge impact on global health; therefore, alternate methods apart from insulin injection are being explored to cure diabetes. Therefore, this review mainly focuses on the current status and therapeutic potential of stem cells mainly mesenchymal stem cells (MSCs) for Type 1 diabetes mellitus in preclinical animal models as well as humans. METHODS: Current treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Meta-analyses of studies on SCs therapy indicated a certain potential to treat liver cirrhosis [3][4][5], chronic liver disease [6], inflammatory bowel disease [7] and ischemic heart disease [8]. SCs therapy also showed a potential effect to halt or abolish the autoimmune destruction of β cells and to generate functional β cells which could achieve optimized glycemic control in T1DM [9][10][11][12][13]. Our systematic review and meta-analysis aims to explore the efficacy and safety of stem cells transplantation (SCT) in patients with T1DM.…”
mentioning
confidence: 99%
“…Meta-analyses of studies on SCs therapy indicated a certain potential to treat liver cirrhosis [3][4][5], chronic liver disease [6], inflammatory bowel disease [7] and ischemic heart disease [8]. SCs therapy also showed a potential effect to halt or abolish the autoimmune destruction of β cells and to generate functional β cells which could achieve optimized glycemic control in T1DM [9][10][11][12][13]. Our systematic review and meta-analysis aims to explore the efficacy and safety of stem cells transplantation (SCT) in patients with T1DM.…”
mentioning
confidence: 99%
“…As for the culture conditions, studies on the proliferation and characteristics of the cells according to the biological and physical culture conditions may be carried out such as the components of the culture medium, the continuous supply of new micro-carrier, and the stirring speed. Mass production of diverse cells like mesenchymal stems, keratinocytes and chondrocytes [25][26][27] is expected to be employed as sources for tissue engineering of bone, cartilage, blood vessels and skins by using diverse recent technologies such as 3D bioprinting [28,29], microchips, hydrogels and others [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these well‐developed protocols require many weeks (some up to 8 weeks) of in vitro culture to achieve β‐cell organoids displaying most mature β‐cell specific markers and function. [ 67–69 ] In addition to hPSCs, other sources of cells derived from tissues, such as fetal pancreatic progenitor cells, [ 70 ] mesenchymal stromal cells, [ 71 ] or other progenitor or terminally differentiated cells (e.g., pancreatic ductal cells or hepatocytes), [ 72,73 ] are differentiated or transdifferentiated in vitro to yield insulin‐producing cells.…”
Section: β‐Cell Organoidsmentioning
confidence: 99%